2008
DOI: 10.1620/tjem.214.51
|View full text |Cite
|
Sign up to set email alerts
|

Higher Efficacy of Urinary Bone Resorption Marker Measurements in Assessing Response to Treatment for Osteoporosis in Postmenopausal Women

Abstract: Osteoporosis has reached epidemic proportions. This situation has stimulated the development of biochemical markers to assist in assessing osteoporotic risk and monitoring treatment effi cacy. Biochemical markers for assessing the level of bone resorption have been developed during the last few decades. One of the most widely used bone resorption markers is cross-linked N-terminal telopeptides (NTX). Measurements of urinary and serum NTX provide indications of the level of bone resorption during osteoporosis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Serum NTX decreases significantly after antiresorptive therapies, but it is less sensitive than urinary NTX in detecting changes induced by such therapies [15]. The reason for this is unknown, and it is still unclear whether dietary intake of collagen can interfere with serum NTX levels.…”
Section: Markers Of Bone Resorptionmentioning
confidence: 99%
“…Serum NTX decreases significantly after antiresorptive therapies, but it is less sensitive than urinary NTX in detecting changes induced by such therapies [15]. The reason for this is unknown, and it is still unclear whether dietary intake of collagen can interfere with serum NTX levels.…”
Section: Markers Of Bone Resorptionmentioning
confidence: 99%
“…Specific biochemical indicators for bone turnover, including bone formation markers (B-ALP; Osteocalcin et al), and bone resorption markers (NTx; Tartrate-resistant acid phosphatase-5b, TRCAP-5b; and Carboxy-terminal collagen crosslinks, CTX etc), might be used as index for disease progression of osteoporosis[4][6]. These sensitive and validated biochemical markers can offer an alternative to well-accepted BMD test to monitor disease progression of osteoporosis and therapeutic treatment [7], [8]. The disadvantage of the biochemical markers is that they only reflect the alteration of bone formation or bone resorption, while the incidence of osteoporosis is attributed to the dual outcomes of bone formation and resorption.…”
Section: Introductionmentioning
confidence: 99%
“…[Mean ± SD] of body mass index [BMI], waist circumference [WC] and fat% for the studied groups are shown in Table (1). The results showed that WC of A group is significantly higher than B and control groups, [P < 0.001], Also WC of B group is significantly higher than control groups, [P < 0.…”
Section: Resultsmentioning
confidence: 99%
“…Osteoporosis is a systemic disease characterized by low bone mass and micro architectural deterioration of bone tissue, resulting in an increased risk of fracture and has touch rampant proportions [1]. According to WHO, 30% of postmenopausal women and 70% of women aged above 80 are affect by osteoporosis [2].…”
Section: Introductionmentioning
confidence: 99%